The mechanism of after-runner storm surge along the Northern coast of Vietnam - Thuy, Nguyen Ba (Vietnam Journal of Marine Science and Technology, 2017)
In this study, the mechanism of sea level rise along the Northern coast of Vietnam after the landfall of the Typhoon Kalmaegi (September/2014) at Quang Ninh province was analyzed based on the observation data and the results of a coupled model of surge, wave and tide (called SuWAT), by using asymmetric and symmetric wind and pressure fields. For the asymmetric wind and pressure field, the Weather Research and Forecasting (WRF) model was used, while for the symmetric wind and pressure field, a parametric wind and pressure model was used. In the case using wind fields from the WRF model, the case that did not consider the effect of tail wind field after the typhoon landfall was also conducted in order to assess the role of the wind field before and after the typhoon landfall on the surge. The results showed that the case using wind and pressure field from the WRF model showed better agreement with observation data, because the WRF model well simulated the wind and pressure field before and after the typhoon landfall. The strong tail wind mainly caused the high surge in the area. This research result will be useful in warning and forecasting storm surges in the area.